Video branding untuk promosi usaha mikro kecil menengah (UMKM) - Wahyuni Eka Sari; Yulianto Yulianto; Eko Junirianto; Annafi Franz; Syafei Karim; Ida Maratul Khamidah (University of Islam Malang, 2021)
Nowadays, Branding or marketing share has evolved from creating images to video. The appropriate videos promotions can increase consumer interest in buying products. The suitable video can provide an positive image to consumers of a product or service. However, there are many obstacles in making interesting branding with video, such as the technique of taking pictures and creating an interesting storyline, the ability to package interesting videos such as editing sound and images, dubbing and then adding text. Solution for the problem, a community service program was carried out by the Politeknik Pertanian Negeri Samarinda to owners of micro, small and medium businesses (UMKM) in Samarinda. Implementation of this activity is carried out for a one-day workshop and then online mentoring for one week. The method of implementation is with lectures, practices, discussions and then questions and answers. This activity was attended by 30 participants. From 30 participants there were 28 participants who succeeded in making a video branding with a duration of 1 to 2 minutes.